MACCANNELL RE-VISITED: A CRITICAL APPROACH TO STRUCTURALSIM - Maximiliano E. Korstanje (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2012)
From his publication, the Tourist, Dean Maccannell has shed light on an entire generation. His legacy opened a new focus of attention in the cultural studies of geography, territory, authenticity and mobility. However, his negative view about tourism as an alienable activity paved the ways for the trivialization of tourism as a scientific discipline. This essay review not only is aimed at reviewing deeply from various works, ranging from the Tourist to Empty meeting grounds, but also we focus on the methodological inconsistencies of structuralism to be applied on tourist-related studies. Our thesis is that Maccannell misunderstood the real nature of tourism and its difference from the tourist destination. His outcomes are illustrative to examine the life of tourist destinations but are invalidated at time of studying tourism from a macro-sociological perspective. Maccannell is a hero of tourism applied research because of his merit; our efforts are placed to debunk his contributions.